Providing equity-oriented care and services: Perspectives of primary care nurses working in Nunavik Inuit communities - Anne-Renée Delli Colli; Amélie Blanchet Garneau (York University Libraries, 2024)
Health inequities experienced by Indigenous Peoples are the consequence of unbalanced structural determinants of health, mainly due to systemic racism and colonialism. Primary care registered nurses face multiple challenges, including lacking resources to care for these communities and address health inequities. This study aimed to explore equity-oriented care and services from the perspectives of primary care registered nurses working in Nunavik (Northern Quebec, Canada) Inuit communities. We used a critical postcolonial perspective and an interpretive descriptive design. We conducted semi-structured interviews with ten participants and thematically analyzed the data collected. The results showed dynamic conceptualizations of equity-oriented care and services that shaped how participants see the northern colonial context, the healthcare accessibility, and the nursing care approach within Inuit communities. From these findings, we call for accountability measures like antiracist policies to promote transformational changes toward health equity.